Illustration Book Design to Introduce the Legend of Tuk Jimat Bende in Bumijawa Village - Nur Zaidah Padlun; Pratama Bayu Widagdo (Gorga : Jurnal Seni Rupa, 2025)
This research aims to introduce the story of the Legend of Tuk Jimat Bende of Bumijawa Village by designing an illustrated book. The design method has two stages: the preparation stage, which includes data collection, data analysis, synthesis, and determination of the design object, and the creation stage, which includes pre-production, production, and post-production. Data was collected using interview instruments, observations, documentation, and questionnaires to support the work process. The data obtained was analyzed using 5W+1H questions, which continued in the synthesis process. The design results at the stage of creating works in the pre-production process are in the form of design concepts that produce keywords to make the design process more manageable. Verbal concepts take the form of text narratives. These have been processed and included in an illustrated book. According to the target audience, the media and visual concept is an A5 illustration book with digital techniques and a semi-realist visual style. The production process involves creating digital sketches and colouring them in warm tones. The editing process combines illustrations and narratives. Post-production related to social media platforms is used as a medium to introduce legendary stories through electronic books or e-books. In terms of technology, it is expected to disseminate information about legendary stories, which helps preserve the region's cultural heritage. Through illustrated books, the legend of Tuk Jimat Bende slowly brought regional traditions to be widely known.